Cardiovascular manifestations in Marfan syndrome and related diseases; multiple genes causing similar phenotypes. (10th July 2014) - Cook, J.R.; Carta, L.; Galatioto, J.; Ramirez, F.
<x xml:space="preserve">Abstract</x> Cardiovascular abnormalities are the major cause of morbidity and mortality in Marfan syndrome (MFS) and a few clinically related diseases that share, with MFS, the pathogenic contribution of dysregulated transforming growth factor β (TGFβ) signaling. They include Loeys–Dietz syndrome, Shprintzen–Goldberg syndrome, aneurysm–osteoarthritis syndrome and syndromic thoracic aortic aneurysms. Unlike the causal association of MFS with mutations in an extracellular matrix protein (ECM), the aforementioned conditions are due to defects in components of the TGFβ pathway. While TGFβ antagonism is being considered as a potential new therapy for these heritable syndromes, several points still need to be clarified in relevant animal models before this strategy could be safely applied to patients. Among others, unresolved issues include whether elevated TGFβ signaling is responsible for all MFS manifestations and is the common trigger of disease in MFS and related conditions. The scope of our review is to highlight the clinical and experimental findings that have forged our understanding of the natural history and molecular pathogenesis of cardiovascular manifestations in this group of syndromic conditions.